Postglacial gravity change in Fennoscandia - three decades of repeated absolute gravity observations - Olsson, Per-Anders; Breili, Kristian; Ophaug, Vegard; Steffen, Holger; Bilker-Koivula, Mirjam; Nielsen, Emil; Oja, Tõnis; Timmen, Ludger (Oxford University Press, 2019)
For the first time, we present a complete, processed compilation of all repeated absolute gravity (AG) observations in the Fennoscandian postglacial land uplift area and assess their ability to accurately describe the secular gravity change, induced by Glacial Isostatic Adjustment (GIA). The dataset spans over more than three decades and consists of 688 separate observations at 59 stations. Ten different organisations have contributed with measurements using 14 different instruments. The work was coordinated by the Nordic Geodetic Commisson (NKG). Representatives from each country collected and processed data from their country, respectively, and all data were then merged to one dataset. Instrumental biases are considered and presented in terms of results from international comparisons of absolute gravimeters. From this dataset, gravity rates of change (g_dot) are estimated for all stations with more than two observations and a timespan larger than two years. The observed rates are compared to predicted rates from a global GIA model as well as the state of the art semi-empirical land uplift model for Fennoscandia, NKG2016LU. Linear relations between observed g_dot and the land uplift, h_dot (NKG2016LU), are estimated from the absolute gravity observations by means of weighted least squares adjustment (WLSA) as well as weighted orthogonal distance regression (WODR). The empirical relations are not significantly different from the modelled, geophysical relation g_dot = 0:03 - 0:163(+-0.016)h_dot. We also present a g_dot -model for the whole Fennoscandian land uplift region. At many stations, the observational estimates of g_dot still suffer from few observations and/or unmodelled environmental effects (e.g. local hydrology). We therefore argue that, at present, the best predictions of GIA-induced gravity rate of change in Fennoscandia are achieved by means of the NKG2016LU land uplift model, together with the geophysical relation between g_dot and h_dot.